Algorithm of Plastic Concrete Crack Resistance is Calculation under Capillary Shrinkage Using Generalizing Criteria - S. N. Leonovich (Наука и техника)
The method of concrete crack-resistance prediction at early age is developed at capillary shrinkage with use of approaches of fracture mechanics, which is guided by the concept of accumulation of defects in structure in the form of capillaries and cracks to their critical concentration of Cc. At the same time process at two stages is considered: on the first – process of formation and growth of defects and on the second – the process, which is directly accompanying destructions (fragmentation) at critical concentration of defects. As a theoretical basis of a method physical ideas of the increment volume mechanism of hollowness of cracks in the concrete model, presented as two-level structure are accepted: a matrix of the hardened cement stone with inclusions and emptiness of various form (crack) as result of the external influences, changing the intense deformed state. The main criterion of a method – the generalized total parameter of crack-resistance calculated on the basis of model schemes of growth, association, localization of cracks system, their classification by types and relative quantity in volume at the initial concentration increasing to critical, that is caused by physical processes of capillary shrinkage is established. Being based on the considered regularities of process of concrete destruction, it is offered to divide all defects of structure, both initial, and developed as a result of power and not power influences, into 5 main types. The amount of pores and cracks of the first four types depends on concrete porosity, and type V – and on the volume content of grains of small or coarse aggregate. To each type of damages, there corresponds the stress intensity factor, extent of influence and which value on the general crack resistance of material depend on quantity of this type of pores and cracks in concrete volume. The new evidence-based algorithm of crack resistance calculation at concrete shrinkage at early age by the generalized criterion, which contains the sequence of operations of calculation as for selection of structure, taking into account the factors, influencing capillary pressure and according to characteristics of properties of concrete components, its technological parameters, and for residual resource definition of concrete on its structure and properties, and also on the samples, which are selected from structures at early age is offered.